Analisis Tingkat Kepuasan Pengguna Aplikasi Grabfood Dilingkungan Universitas Bina Insan menggunakan Metode Importance Performance Analysis (IPA) - Efendi, Shelly Nadia; Zulfauzi, Z; Satrianansyah, S (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The problem in this study is that the use of services in the Grabfood application still has many shortcomings, including the process of finding drivers who will pick up consumer orders, the rates set by Grabfood are still too expensive, the lack of promos given to consumers, and the lack of existing restaurants. in the city of Lubuklinggau which is registered in the Grabfood application, then whether this problem is a factor or not or customer satisfaction with the grabfood application and will be examined using the Importance Performance Analysis (IPA) method with Service Quality variables (Tangiabels, Reliability, Responsiveness, Assurance, Empathy, Product Quality, Price). This study also uses 2 data including primary data and secondary data. Primary data is observation method (directly involved), interview method (interview), documentation and questionnaire method. While secondary data are journals and books. From the results of the analysis there were 2 items that were considered good, and there were 4 items that were considered not good and this should be improved in the future. The score for customer satisfaction for the Grabfood application at Bina Insan University is 94%, which means it is satisfactory.